2009
DOI: 10.1371/journal.pbio.1000086
|View full text |Cite
|
Sign up to set email alerts
|

Cryptochrome Mediates Light-Dependent Magnetosensitivity of Drosophila's Circadian Clock

Abstract: Since 1960, magnetic fields have been discussed as Zeitgebers for circadian clocks, but the mechanism by which clocks perceive and process magnetic information has remained unknown. Recently, the radical-pair model involving light-activated photoreceptors as magnetic field sensors has gained considerable support, and the blue-light photoreceptor cryptochrome (CRY) has been proposed as a suitable molecule to mediate such magnetosensitivity. Since CRY is expressed in the circadian clock neurons and acts as a cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
208
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(221 citation statements)
references
References 53 publications
(95 reference statements)
10
208
3
Order By: Relevance
“…Largely based on this fact, it was also proposed that electron transfer through the Trp triad is the primary photochemical event in dCRY signaling (25). Moreover, the electron transfer through the Trp triad to flavin generates a charge separated radical pair, and this has led to the proposal that dCRY acts not only as a circadian photoreceptor but also as a magnetoreceptor (23,24). In support of a magnetosensory function of dCRY, it was found that Drosophila was capable of sensing the magnetic field and that the magnetosensory function was lost in dCRY null mutants (23,24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Largely based on this fact, it was also proposed that electron transfer through the Trp triad is the primary photochemical event in dCRY signaling (25). Moreover, the electron transfer through the Trp triad to flavin generates a charge separated radical pair, and this has led to the proposal that dCRY acts not only as a circadian photoreceptor but also as a magnetoreceptor (23,24). In support of a magnetosensory function of dCRY, it was found that Drosophila was capable of sensing the magnetic field and that the magnetosensory function was lost in dCRY null mutants (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the electron transfer through the Trp triad to flavin generates a charge separated radical pair, and this has led to the proposal that dCRY acts not only as a circadian photoreceptor but also as a magnetoreceptor (23,24). In support of a magnetosensory function of dCRY, it was found that Drosophila was capable of sensing the magnetic field and that the magnetosensory function was lost in dCRY null mutants (23,24). However, mutations in the Trp triad did not affect the magnetosensory capacity of the fly (23), raising some doubts about the role of electron transfer through the Trp triad in photosensory (circadian and magnetic) function of dCRY.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now established that electromagnetic fields, even if very weak, can have an influence on basic biological functions, such as circadian rhythmicity of Drosophila's locomotor activity (Yoshii et al, 2009), orientation and navigation in birds (Wiltschko & Wiltschko, 2005;Rodgers & Horea, 2009;Wu & Dickman 2012) and larval development of the Japanese newt, Cynops pyrrhogaster (Asashima et al, 1991). It is also known that electromagnetic shielding causes sharp phase shifts and amplitude changes of infradian rhythmicity of the pain sensitivity in land snails Helix albescens (Kostyuk & Temuryants, 2009) and of mobility in the planarian Dugesia tegrina (Yarmolyuk, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Cryptochromes have lost the ability to repair DNA, but they play a key role in controlling the growth and development in plants and in the circadian clock in plants and animals (4). Furthermore, recent evidence suggests that cryptochromes are likely to function as light-dependent magnetic field sensors, used for example by insects or migratory birds and fish for directional responses (5)(6)(7).…”
mentioning
confidence: 99%